The rise of the "redback" and the People's Republic of China's capital account liberalization: An empirical analysis of the determinants of invoicing currencies - Hiro Ito; Menzie Chinn (Asian Development Bank Institute (ADBI), 2014)
We investigate the determinants of currency choice for trade invoicing in a cross-country context while focusing on the link between capital account liberalization and its impact on the use of the renminbi (RMB). We find that while countries with more developed financial markets tend to invoice less in the US dollar, countries with more open capital accounts tend to invoice in either the euro or their home currency. These results indicate that financial development and financial openness are among the keys to challenging the US dollar dominance in general, and to internationalizing the RMB for the People's Republic of China (PRC). Our model also suggests that the share of the RMB in export invoicing should have been higher than the actually observed share of less than 10%. The underperformance of RMB export invoicing can be attributed to the inertia in the choice of currency for trade invoicing; once a currency is used for trade invoicing or settlements, it becomes difficult for traders to switch from one currency to another. This same phenomenon was also observed in the cases of the Japanese yen and the euro at their inceptions as international currencies. Our model predicts that the share of RMB invoicing for the PRC's exports will rise to above 25% in 2015 and above 30% in 2018, whether or not the PRC implements drastic financial liberalization. As the near future path of RMB use is also expected to be inertial, these forecasts are probably at the upper end of the actual path of RMB export invoicing.
Keywords: F32; F41; 330; RMB internationalization; capital account liberalization; US dollar; export invoicing; currency invoicing; settlement currency